Idiopathic sudden sensorineural hearing loss and acute low-tone sensorineural hearing loss: a comparison of the results of a nationwide epidemiological survey in Japan. (10th March 2017) - Yoshida, Tadao; Sone, Michihiko; Kitoh, Ryosuke; Nishio, Shin-ya; Ogawa, Kaoru; Kanzaki, Sho; Hato, Naohito; Fukuda, Satoshi; Hara, Akira; Ikezono, Tetsuo; Ishikawa, Kotaro; Iwasaki, Satoshi; et al.
Abstract: Objectives: The aim of this study was to investigate the differences between idiopathic sudden sensorineural hearing loss (SSNHL), and acute low-tone sensorineural hearing loss (ALHL) using the results of a nationwide survey database in Japan and to analyze the variables associated with their clinical features and the severity of hearing impairment, treatment, and prognosis. Methods: Participants were patients registered between April 2014 and March 2016 in a multicenter epidemiological survey database involving 30 university hospitals and medical centers across Japan. Statistical analysis was performed to clarify the factors associated with their clinical characteristics and the severity of hearing impairment, treatment, and prognosis. Results: Idiopathic SSNHL and ALHL differed significantly in terms of male-to-female ratio, age distribution, and time from onset to start of treatment. The treatment methods and hearing prognosis also differed markedly between the two diseases. A majority (92%) of idiopathic SSNHL patients were administered some type of corticosteroid, while half of the ALHL patients received corticosteroids and a diuretic agent. Conclusion: The results suggested that idiopathic SSNHL and ALHL belonged to different categories of inner ear disease.